DESIGN OF MANIPULATOR ROBOT IN UNMANNED GRENADE TAMER (UGT) - Ayip Rivai Prabowo; Endro Prasetijoadi; Dueng Deriva; Wawan Kusdiana (JOURNAL ASRO, 2020)
Low safety factor in the Standard Operating Procedure (SOP) in handling grenades that fail to explode at the training location can be fatal for personnel and instructors. In a previous study, a stick manipulator was designed. However, this tool has disadvantages because the operator is too close to explosives. By considering the security of personnel, the authors make "Design Robot Manipulator Build on Unmanned Grenade Tamer (UGT)". This tool is used to assist trainers and instructors in the implementation of laying explosives as a procedure for handling grenades that do not explode properly in position. The mechanism of this tool is made to complement the base tank that is driven by a robot remote control system that moves using a servo motor as an actuator. The total length of the horizontal arm stretch is 780 mm and 795 mm for the vertical stretch. Arm foundation is designed capable of rotating as far as 120⁰. Link 1 moves 150 °, link 2 150 °, Link 3 1801, and wrist roll 90 °. The force acting on link 1 is 16.758N in the direction of the y-axis parallel force, torque is 5.5 Nm and with an angular acceleration of 142rad / s². On the link 2 force of 16.66N, the direction of the force is parallel to the y axis, torque of 9.4 Nm and angular acceleration of 496rad / s². And on the 3 link force of 14.7N of torque of 3.3 Nm and angular acceleration of 293rad / s². The gripper gripping force is 1,158 kgf which is driven by a servo motor with a minimum torque of 5.42 Nm. Keywords: Robot arm, Torque, Gripper